Induction of non-specific human suppressor cells in vitro by defined Onchocerca volvulus antigens. - Ouaissi, M A (1983)
In the present study the activity of Onchocerca volvulus total antigens (OVA) on the proliferative response of human lymphocytes from healthy donors was investigated. Normal human lymphocytes were cultured for 72 h with polyclonal activators, phytohaemagglutinin (PHA) or pokeweed mitogen (PWM), together with OVA, and thymidine uptake was measured. The proliferation of normal lymphocytes was markedly inhibited by the parasite antigens. The inhibition was not attributable to a cytotoxic effect of OVA, since at least 80% viable cells were recovered at the end of cell cultures. The inhibition was not abrogated by removal of the adherent cell population. The passage of OVA through immunosorbent column containing human antibodies to O. volvulus significantly reduced the suppressive activity of OVA. The in vitro response to mitogens (PHA, PWM) of normal human lymphocytes was suppressed by co-culture with allogeneic or syngeneic lymphocytes, which had previously been exposed for 72 h to OVA. The suppression was not abrogated by the irradiation of mononuclear cells before the exposure to OVA. A significant reduction of the suppression was however observed when OVA pre-treated cells were T cell depleted by centrifugation of E rosettes. Thus, parasite antigens, which are recognized by antibodies in infected human sera may participate in the modulation of the cellular immune response during O. volvulus infection by inducing suppressor cells. This suppression could in addition contribute to the survival of the parasite in its host.